Vesico-cervical fistula following normal vaginal delivery: case report and management overview - Koothan, Vijaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Vesico-uterine fistula is an uncommon pathological communication developing between the uterus or cervix and the urinary bladder especially in traumatic caesarean sections. We presented a case of vesico-cervical fistula who presented after 18 years of occurrence of fistula and successful repair. Clinical diagnosis may be delayed due to varied presentations and evaluation may require more than one modality of investigation. The choice of treatment surgical or conservative management depends on the location size and number of the fistula. Surgical outcomes of open laparotomy, laparoscopic and robotic surgery have been successful. Obstetric outcomes of post repair patients have had successful pregnancies.